Bridging Financial Forecasting and Budget Management: New Approaches for Modern Enterprises - Lipelis, Mikhail (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The study aims at uncovering the linkages between financial forecasting accuracy and budget performance in modern enterprises, pointing at the crucial role of integration, managerial and economic conditions, on both suggesting the possible causes and prognosis of budgeting performance decline. The research uses panel data from 2020 to 2024 of ten leading U.S. companies across different industries and applies a fixed effects econometric model to estimate the effect of important internal and external factors on budget variance. The results show that higher forecasting accuracy, stronger integration among financial planning functions, and more agile managers are linked with better budget outcomes. JPMorgan Chase, Apple and Microsoft were companies with better internal systems and thus better control of deviations in budgets whereas Tesla and Boeing were more open to fluctuations in their systems making budget deviations challenging. The study underlines the importance of focus of the enterprises for not only to invest in the predictive tools but also to be in line with the strategic decision making and financial execution processes for the insulation of the resilience and the financial discipline of the enterprise in a dynamic setting.